Who is educating our future Medical Laboratory Scientists? A perspective of AIMS accredited Medical Laboratory Science programs in Australia. - Donkin, Rebecca; Swanepoel, Libby; Gusset, Rebecca (Australian Journal of Medical Science)
The primary qualification to obtain employment as a Medical Laboratory Scientist is a university undergraduate degree in Medical Laboratory Science (MLS) or equivalent. University education for this degree is provided by academics who may not have a qualification in MLS or have experience as a Medical Laboratory Scientist. Due to the paucity of literature that describes the demographics of MLS academics, their qualifications, and previous experience as a Medical Laboratory Scientist, a descriptive cross-sectional study design was used to attempt to attain this information. Ten AIMS accredited academic programs participated in the study. Despite reporting experience in teaching over 100 MLS subjects, only a third of the academics had MLS qualifications and over half of the respondents had never worked in a pathology laboratory. Further research is needed to understand how this contributes to the employment outlook in the pathology industry and the graduate student outcomes.